Dynamic Model of Urban Public Cemeteries Development Strategy: Case Study of Manado City, Indonesia - Hendrik Suryo Suriandjo; Doly Herling Tiagas; Felly Ferol Warouw; Aristotulus Ernst Tungka (Jurnal Wilayah dan Lingkungan, 2026)
The development of a policy strategy for public cemeteries through System Dynamics (SD) modeling is crucial in addressing the pressing issue of limited urban land. This research aims to formulate long-term solutions for the future cemeteries needs. Data was collected through field observations, surveys, and focus group discussions. The analysis employed a system dynamics approach, formulating two different scenarios. Two policy scenarios were developed to evaluate cemetery land sustainability. Scenario 1 represents a baseline condition with existing burial practices and no additional policy intervention. Scenario 2 incorporates integrated interventions, including land expansion, vertical burial implementation, and mortality reduction through public health improvements. The results confirm that SD provides a robust framework for conceptualizing cemetery provision as a dynamic urban policy issue rather than a static spatial allocation. Scenario Two emerges as the optimal strategy up to 2045, reducing annual deaths by 313 individuals (from 5,275 to 4,961), lowering the Crude Death Rate from a high to a moderate category, and significantly easing pressure on cemetery land. This scenario decreases the required cemetery land from 42.99 hectares to approximately 11.86 hectares and increases land carrying capacity by 16.62 hectares relative to the projected deficit. These findings demonstrate that health-oriented policies can function as indirect spatial planning instruments, extending conventional approaches to urban land management under conditions of scarcity.